TECHNOLOGICAL AWARENESS AS A PREDICTOR OF ACCOUNTING STUDENTS’ ACADEMIC ETHICS AMID THE DIGITAL TRANSFORMATION OF HIGHER EDUCATION - Etty Harya Ningsi; Langgeng Prayitno Utomo; Setia Budi Kurniawan; Grahita Chandrarin; Harianto Respati (UPT Publikasi Ilmiah UNISBA, 2025)
This study investigates the role of technological awareness in predicting the academic ethics of accounting students during the digital transformation of higher education. Using a quantitative survey design, data are collected through questionnaires from accounting students at Battuta University who participate in digital learning. The analysis employs multiple linear regression, classical assumption tests, t-tests, and the coefficient of determination, processed using SPSS. Results show that technological awareness significantly and positively influences students’ academic ethics. Students with higher technological awareness demonstrate a stronger understanding of academic integrity and are less prone to unethical behaviors such as plagiarism and dishonesty. The study concludes that integrating technological literacy into the accounting curriculum supports ethical behavior and strengthens academic conduct in the digital learning environment.